A imagem que vivi: o lugar da Arte em minha trajetória enquanto artista-professor - SILVA, Marcos Vinicius Gomes (2022)
The present work is the result of the nuances between life experiences and artistic creation. Focused on the personal creative process, the research aims to understand and analyze the influences of the cultural and geographic context which I lived and its direct connection with the way in which I observe, represent and reframe the world through the pandemic/Covid-19 reality. Through this, I try to emphasize the importance of drawing, games in my childhood, the teaching/learning of artistic initiation at school that opened in me territories of sensitivity and creative imagination of my artistic construction, based on reading and image construction . The research is divided into an introduction, three chapters and the final considerations about the research. The results point to the identity meanings of reality such as experiences experienced in the pandemic period involving loneliness, anxiety, affection and healing, which resulted in the elaboration of four images with influences from the context lived in its creation, thus generating the images entitled “A Solitude” , “A Ruptura”, “O Amparo” and “A Cura”, which make up the series “A Paixão do Ordinário”.